Map of the Utilization of Social Media in Forming Student Literation Culture in Makassar - Himayah Himayah (UPT Perpustakaan UIN Alauddin Makassar, 2020)
ABSTRACTThis study aims to see a map of social media use in shaping a literacy culture among students in Makassar. The ease of accessing information sources, copying and pasting information to other places, or sharing information with other parties, has changed students' literacy habits. Using a quantitative approach, this study distributes questionnaires to students via the google docs link. A total of 200 students who have been willing to fill out and return this research questionnaire. The result of this research found that social media has become a necessity for students, especially used for chatting with their friends. Apart from communicating, social media is also used for education, literacy, and fun. Regarding reading and writing literacy habits, social media provides easy access to information providers, so that students use it to meet their needs without having to bother, especially to re-read and check reading material. The variety of information changes rapidly, making students feel that they are sufficient to read news headlines without having to read the entire contents of the information. Likewise, regarding the credibility of news sources, it is not an important thing for students to pay attention to. This shows that the habit of using social media has not been able to help improve literacy skills among students.ABSTRAKPenelitian ini bertujuan melihat peta pemanfaatan media sosial dalam membentuk budaya literasi di kalangan mahasiswa di Makassar. Kemudahan dalam mengakses sumber informasi, menyalin dan menempel informasi ke tempat lain, atau membagikan informasi kepada pihak lain, telah mengubah kebiasaan mahasiswa dalam berliterasi. Dengan menggunakan pendekatan kuantitatif, penelitian ini menyebarkan angket kepada mahasiswa melalui link google docs. Sebanyak 200 mahasiswa yang telah bersedia mengisi dan mengembalikan angket penelitian ini. Hasik penelitian ini menemukan bahwa media sosial sudah menjadi kebutuhan mahasiswa, terutama digunakan untuk mengobrol dengan teman-teman mereka. Selain berkomunikasi, media sosial juga digunakan untuk pendidikan, literasi dan kesenangan. Terkait kebiasaan literasi baca tulis, media sosial dengan memberikan kemudahan dalam melakukan akses ke penyedia informasi, sehingga mahasiswa memanfaatkannya untuk memenuhi kebutuhan tanpa harus bersusah payah, terutama untuk membaca ulang dan memeriksa bahan bacaan. Ragam informasi yang terus berubah dengan cepat, membuat mahasiswa merasa cukup membaca judul-judul berita tanpa harus membaca keseluruhan isi informasi yang ada. Demikian pula mengenai kredibilitas sumber berita, tidak menjadi hal yang penting untuk diperhatikan oleh mahasiswa. Ini menunjukkan bahwa kebiasaan menggunakan media sosial, belum dapat membantu meningkatkan kemampuan literasi di kalangan mahasiswa..